Binding interactions between prazosin and α1A-adrenoceptor: investigation on the thermodynamic behaviors and the binding mechanism by high performance affinity chromatography. Issue 8 (21st April 2015) - Wang, Jing; Li, Qian; Yang, Lingjian; Zhang, Yajun; Yu, Jie; Zhao, Xinfeng; Zheng, Jianbin; Zhang, Youyi; Zheng, Xiaohui
<x xml:space="preserve">Abstract</x> The interactions of prazosin binding to immobilized α1A-adrenoceptor were studied by frontal analysis and molecular docking.